Calculation of internal heat source and thermal gradient of cylindrical traction battery with measured surface temperature and heat flux - Wang, Haimin; Zhu, Zexu; Ji, Zhiyuan; Hu, Feng; Lin, Hao (International journal of thermal sciences, 2023)
In the process of charging and discharging, the traction battery not only experiences electrochemical reactions, but also includes many side reactions, the typical phenomenon of which is the rise of battery temperature. In order to study the characteristics of the internal heat source and the distribution of the temperature field of a cylindrical battery, a one-dimensional (radius direction) heat transfer model is established in this work. Then, the temperature and heat flux measured on the external surface of the battery is used to calculate the internal heat source and temperature distribution, so as to quantify the thermal gradient in the diameter direction. In order to verify the feasibility of the model, a small incision is cut at the bottom of the battery, a thermocouple is built in to measure the temperature of the central position inside the battery, and the measured temperature is compared with the calculated temperature. The results show that the calculated results of the model have high reliability. In addition, the proposed model is also used to calculate the temperature of its internal central position at a higher ambient temperature (40 °C) and a lower ambient temperature (−10 °C). It is found that the calculated results are very close to the measured results at the ambient temperature of 40 °C, but the difference between the two was large at the ambient temperature of −10 °C. •Heat transfer model of a cylindrical cell with internal heat source was established.•Calculating internal temperature with measured surface temperature and heat flux.•The accuracy of model is verified by the measured internal center temperature of cell.•The calculation method has a high accuracy in the ambient temperature of 20 °C–40 °C.